Profile of Student’s Cultural Concern Through Science Learning Based on Pacu Jalur Kuantan Singingi - Andika Febrian; Andi Rahmawati; Insih Wilujeng; Zuhdan Kun Prasetyo; Sofyan Dwi Nugroho (Jurnal Penelitian Pendidikan IPA, 2023)
Science is a lesson that discusses various natural phenomena scientifically and systematically in life. Along with the times, science has undergone many transformations in improving the quality of learning, one of which is local culture-based science learning. The rapid flow of globalization of foreign cultures that enter Indonesia, making the youth generation begin to forget local culture as a noble identity. This study aims to see the effect of local culture-based science learning on the profile of cultural awareness of junior high school students. The research method used is quantitative research by giving post-test to two different classes that have implemented the learning. The two classes consisted of 31 people in the modeling class and 29 people in the implementation class. The sampling technique used was cluster random sampling. The results obtained were then analyzed and discussed descriptively quantitatively. The results show that the application of Kuantan Singingi Pacu Jalur culture-based learning can affect the achievement of students' cultural concern profile by obtaining an average score of high categories in the modeling class and very high in the implementation class. Although the average results are in two different categories, when tested through non-Parametric statistics the two results do not have a significant difference